Pressure-induced reversal of Peierls-like distortions elicits the polyamorphic transition in GeTe and GeSe - Tomoki Fujita; Yuhan Chen; Yoshio Kono; Seiya Takahashi; Hidetaka Kasai; Davide Campi; Marco Bernasconi; Koji Ohara; Hirokatsu Yumoto; Takahisa Koyama; Hiroshi Yamazaki; Yasunori Senba; et al. (Nature Communications)
Abstract While polymorphism is prevalent in crystalline solids, polyamorphism draws increasing interest in various types of amorphous solids. Recent studies suggested that supercooling of liquid phase-change materials (PCMs) induces Peierls-like distortions in their local structures, underlying their liquid-liquid transitions before vitrification. However, the mechanism of how the vitrified phases undergo a possible polyamorphic transition remains elusive. Here, using high-energy synchrotron X-rays, we can access the precise pair distribution functions under high pressure and provide clear evidence that pressure can reverse the Peierls-like distortions, eliciting a polyamorphic transition in GeTe and GeSe. Combined with simulations based on machine-learned-neural-network potential, our structural analysis reveals a high-pressure state characterized by diminished Peierls-like distortion, greater coherence length, reduced compressibility, and a narrowing bandgap. Our finding underscores the crucial role of Peierls-like distortions in amorphous octahedral systems including PCMs. These distortions can be controlled through pressure and composition, offering potentials for designing properties in PCM-based devices.